The Effect of Work Life Balance and Green Environment on Employee Performance at PT PYX Solusi Teknologi: JEL Classification: M12, M14, J24, J28, Q56 - Carens Afferio Taebenu; Rolyana Ferinia Pintauli (Journal of Management and Administration Provision, 2026)
The purpose of this study was to investigate how employees at PT. PYX Solusi Teknologi perform in relation to work-life balance and the green environment. Indicators of the factors of Work Life Balance, Green Environment, and Employee Performance were measured using a closed questionnaire with a Likert scale. All PT. PYX Solusi Teknologi employees were included in the study's population. The accidental sampling method was used to select 116 respondents. The operational definitions of the variables include Work Life Balance, which measures the balance between work and personal obligations; Green Environment, which assesses healthy working conditions that promote environmental sustainability; and Employee Performance, which gauges aspects of quantity, quality, timeliness of task completion, work effectiveness, independence at work, and interpersonal skills. The outer model, inner model, R-square, and path coefficient were all tested using the data analysis method (SEM-PLS). The assertion that family support leads to better performance at work has the greatest value of the work-life balance variable indicator, according to descriptive data. The claim that the presence of a green environment promotes employee care for the environment and enhances comfort at work has the highest value of the green environment variable indicator. The ability to do tasks on schedule and in accordance with goals has the greatest value of the employee performance variable indicator. The study's findings show that employee performance is positively and significantly impacted by both work-life balance and the green environment, both directly and indirectly through the green environment's role as an intervening variable.